A Frequency Multiplier Based on Time Recursive Processing - Perisic, D. M.; Zoric, A. C.; Gavric, Z. (Engineering, Technology & Applied Science Research, 2017)
This paper describes a digital frequency multiplier for a pulse rate. The multiplier is based on the recursive processing of the input and output periods and their time differences. Special emphasis is devoted to the techniques which provide the development of multipliers based on this principle. The circuit is defined by two system parameters. One is the ratio of two clock frequencies and the other is a division factor of a binary counter. The realization of the circuit is described. The region of the system parameters for the stable circuit is presented. The different aspects of applications and limitations in realization of the circuit are considered. All mathematical analyses are made using a Z transform approach. It is shown that the circuit can be also used in tracking and prediction applications. Computer simulations are performed to prove the correctness of the math and the whole approach.